2018
DOI: 10.1093/brain/awy155
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of bradykinesia in Parkinson’s disease

Abstract: Many neurophysiological abnormalities have been described in the primary motor cortex of patients with Parkinson's disease. However, it is unclear whether there is any relationship between them and bradykinesia, one of the cardinal motor features of the condition. In the present study we aimed to investigate whether objective measures of bradykinesia in Parkinson's disease have any relationship with neurophysiological measures in primary motor cortex as assessed by means of transcranial magnetic stimulation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
125
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 69 publications
15
125
0
Order By: Relevance
“…MDS-UPDRS3 scores strongly discriminated PD patients from controls. In contrast, differences in fine motor tests were less pronounced although PD patients displayed larger amplitudes and lower tapping speed than controls in line with other investigations [32,33]. In a large cohort of healthy subjects, we have demonstrated that age is a strong determinant of dexterity [11].…”
Section: Discussionsupporting
confidence: 90%
“…MDS-UPDRS3 scores strongly discriminated PD patients from controls. In contrast, differences in fine motor tests were less pronounced although PD patients displayed larger amplitudes and lower tapping speed than controls in line with other investigations [32,33]. In a large cohort of healthy subjects, we have demonstrated that age is a strong determinant of dexterity [11].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, studies using PAS found that synaptic plasticity may be deficient in the absence of dopaminergic medication in the motor cortex of patients with PD (49, 50). This has been recently shown to correlate with motor performance and be in part reversible by dopamine replacement (51), suggesting not only a pathophysiological link between plasticity and dopamine availability, but also between motor cortical plasticity and akinesia in PD. The human STN receives dopaminergic projections from midbrain dopamine neurons (52).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, repetitive finger tapping is one of the tests most commonly used in the clinical assessment of patients with parkinsonian syndromes. Namely, specific kinematic abnormalities of finger tapping, that is, the amplitude decrement (also known as the sequence effect) are hallmarks of PD [ 25 28 ]. Thus, a better knowledge of the effectiveness of tACS on motor control is essential for future studies in pathological conditions [ 29 ].…”
Section: Introductionmentioning
confidence: 99%